Social pedagogy in modern times - Rosendal Jensen, Niels (Education Policy Analysis Archives, 2013)
The article identifies several key concepts used to describe and categorize social pedagogy. The first section of the paper establishes a framework for considering the diversity that characterizes the field, including reflection on social pedagogy’s theoretical, political and social dimensions. This is followed by a discussion based on a holistic understanding of the interaction between individuals and society, which leads to recognition of the profession’s tendency to present itself with a “Janus face.” The paper concludes by pointing out prospects for further development of social pedagogy in the dialectic between theory/research and pedagogical practice.